What kind of a problem is loneliness? Representations of connectedness and participation from a study of telepresence technologies in the UK - Hughes, Gemma; Moore, Lucy; Hennessy, Megan; Sandset, Tony; Jentoft, Elian E.; Haldar, Marit (Frontiers in Digital Health, 2024)
Loneliness is represented in UK policy as a public health problem with consequences in terms of individual suffering, population burden and service use. However, loneliness is historically and culturally produced; manifestations of loneliness and social isolation also require social and cultural analysis. We explored meanings of loneliness and social isolation in the UK 2020–2022 and considered what the solutions of telepresence technologies reveal about the problems they are used to address. Through qualitative methods we traced the introduction and use of two telepresence technologies and representations of these, and other technologies, in policy and UK media. Our dataset comprises interviews, fieldnotes, policy documents, grey literature and newspaper articles. We found loneliness was represented as a problem of individual human connection and of collective participation in social life, with technology understood as having the potential to enhance and inhibit connections and participation. Technologically-mediated connections were frequently perceived as inferior to in-person contact, particularly in light of the enforced social isolation of the COVID-19 pandemic. We argue that addressing loneliness requires attending to other, related, health and social problems and introducing technological solutions requires integration into the complex social and organisational dynamics that shape technology adoption. We conclude that loneliness is primarily understood as a painful lack of co-presence, no longer regarded as simply a subjective experience, but as a social and policy problem demanding resolution.